2015
DOI: 10.4103/0253-7176.155615
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions are not Affected by 24 Hours of Sleep Deprivation: A Color-Word Stroop Task Study

Abstract: Background:Sleep is an important factor affecting cognitive performance. Sleep deprivation results in fatigue, lack of concentration, confusion and sleepiness along with anxiety, depression and irritability. Sleep deprivation can have serious consequences in professions like armed forces and medicine where quick decisions and actions need to be taken. Color-Word Stroop task is one of the reliable tests to assess attention and it analyzes the processing of information in two dimensions i.e., reading of words an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…The findings of monochrome reading which was found more in stressed group A compared to relaxed group B participants. Our findings of monochrome reading are consistent to previous studies 21,22 25 . Karthikeyan et al 24 assessed Stroop color word test (stressor) for induction of stress and consequently the electrocardiogram and heart rate variability were detected.…”
Section: T-valuesupporting
confidence: 93%
See 2 more Smart Citations
“…The findings of monochrome reading which was found more in stressed group A compared to relaxed group B participants. Our findings of monochrome reading are consistent to previous studies 21,22 25 . Karthikeyan et al 24 assessed Stroop color word test (stressor) for induction of stress and consequently the electrocardiogram and heart rate variability were detected.…”
Section: T-valuesupporting
confidence: 93%
“…The findings of present study showed an increase in time domain in stress persons from exercise 1 to 4 as shown above. The findings are comparable to previous studies[21][22][23][24] . Ghimri et al22 has recently reported a study from Nepal.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Several experimental sleep deprivation studies have reported domain-specific associations with performancebased EFs (Banks and Dinges, 2007;Jackson et al, 2013;Lo et al, 2012). Some studies have reported slower reaction times, but no weakening of inhibitory control in sleepdeprived subjects (Bratzke et al, 2012;Cain et al, 2011;Dixit and Mittal, 2015), while others reported poorer performance in tasks requiring higher executive functions, such as risk-taking (Rossa et al, 2014) or divergent thinking (Vartanian et al, 2014), but with no effect on reaction times.…”
mentioning
confidence: 99%
“…In addition, to test the SD effect on interference control (attending to task-relevant and/or suppressing task-irrelevant information), interference tasks, such as the Stroop (1935), Simon (Simon & Rudell, 1967), and Eriksen flanker tasks (Eriksen & Eriksen, 1974), have often been used. Most related studies have shown that interference effects are not modulated by SD (Bratzke et al, 2012; Cain et al, 2011; Dixit & Mittal, 2015; Grant et al, 2018; Hsieh et al, 2007, 2010; Sagaspe et al, 2006; Tsai et al, 2005), except for two studies reporting increased interference effects after SD (Gevers et al, 2015; Ramdani et al, 2013). The unchanged interference effects seem to suggest that interference control is not modulated by or is insensitive to SD.…”
Section: Interference Effects and Sdmentioning
confidence: 97%